Healthier rhythm, healthier brain? Integrity of circadian melatonin and temperature rhythms relates to the clinical state of brain‐injured patients. (19th March 2019) - Blume, C.; Angerer, M.; Raml, M.; del Giudice, R.; Santhi, N.; Pichler, G.; Kunz, A. B.; Scarpatetti, M.; Trinka, E.; Schabus, M.
Abstract : Background: Healthy circadian rhythmicity has been suggested to relate to a better state of brain‐injured patients and to support the emergence of consciousness in patient groups characterized by a relative instability thereof such as patients with disorders of consciousness (DOC). Methods: Going beyond earlier studies, a systems‐level perspective was adopted and, using multilevel modelling, the joint predictive value of three indices of circadian rhythm integrity derived from skin temperature variations, melatoninsulfate secretion, and physical activity (wrist actigraphy) patterns was evaluated for the behaviourally assessed state [Coma Recovery Scale ‐ Revised (CRS‐R) score] of DOC patients [13 unresponsive wakefulness syndrome; seven minimally conscious (exit) state]. Additionally, it was assessed in a subset of 16 patients whether patients' behavioural repertoire (CRS‐R score) varied (i) with time of day or (ii) offset from the body temperature maximum (BTmax ), i.e. when cognitive performance is expected to peak. Results: The results reveal that better integrity of circadian melatoninsulfate and temperature rhythms relate to a richer behavioural repertoire. Moreover, higher CRS‐R scores are, by trend, related to assessments taking place at a later daytime or deviating less from the pre‐specified time of occurrence of BTmax . Conclusions: In conclusion, the results suggest that therapeutic approaches aimed at improving circadian rhythms in brain‐injured patients are promising and should be implemented in hospitals or nursing homes. Beyond this, it might be helpful to schedule diagnostic procedures and therapies around the (pre‐assessed) BTmax (≈4 pm in healthy individuals) as this is when patients should be most responsive.